Identification of genotype and phenotype of antimicrobial resistance of Escherichia coli isolates from pigs in southern Vietnam - Duy, DT; Anh, NLL; Thoa, NTK; Phitsanuwattana, K; Thongratsakul, S; Carrique-Mas, JJ; Hien, LT; Nam, NTT; Toan, NT (Chulalongkorn University Press, 2021)
Escherichia coli is a primary reservoir of antimicrobial resistance, known chiefly for the container of AMR-encoding genes (ARGs), and poses potential risks to human and animal health. This study investigated AMR phenotypes and ARGs in 90 E. coli isolates from different pig groups in 10 farms in southern Vietnam. The minimum inhibitory concentration (MIC) of 19 common antimicrobial agents was determined, and polymerase chain reaction (PCR) was used to investigate seven ARGs (blaTEM, aadA1, strA, dfrA12, sul3, cmlA and tetA). Cohen’s kappa statistic (κ) was applied to assess the concordance between phenotypic and genotypic profiles. A total of 81.1% of E. coli isolates were multi-drug resistant (MDR). The amphenicol class accounted for the highest resistance (100% isolates), followed by the tetracycline class (97.8%), the quinolones and penicillin classes (85.6% each), sulfonamides (67.8%) and aminoglycosides (63.3%). A greater proportion of isolates from weaner pigs showed resistance to multi-antibiotics (43.0%), followed by growers (39.5%) and finishers (36.3%), although the difference was not significant (P>0.05). The prevalence of ARGs was greatly variable and was highest for aadA1 (98.9%), cmlA (98.9%), blaTEM (97.8%), dfrA12 (97.8%), tetA (97.8%), sul3 (97.8%) and strA (83.3%). No significant correlation between ARGs and phenotypic resistance was identified. The results indicate a great diversity of genotypic and phenotypic AMR profiles in pig E. coli isolates. The lack of correlation might be a reflection of additional genes encoding the observed genotypic profiles or the presence of non-plasmid mediated resistance in many cases.